Resilience Factors of Ukrainian Micro, Small, and Medium-Sized Business - Andrii Dligach; Andriy Stavytskyy (Economies)
Nowadays, businesses in Ukraine face new challenges that the world has never experienced before. Earlier, during the war, countries had to curtail their economic activities, everything operated for the sake of military needs. However, now, within hybrid wars, the country’s economy and its actors have to demonstrate rapid adaptive models and changes in strategies, and sometimes function without strategies at all. Advanter Group conducted a survey of 696 Ukrainian enterprises in the period from 20 December 2023 to 8 January 2024 (a year of full-scale aggression); a direct questionnaire method was used. Key hypotheses (10 hypotheses) regarding the resilience factors of Ukrainian businesses during the period of the full-scale invasion were tested using statistical analysis methods. Statistically significant differences were established in various aspects of the functioning of SMBs. Based on the research, it is concluded that reforms in the legal sphere, aimed at facilitating conditions for business and protecting the rights of enterprises, are an urgent necessity for the further development of the economy of Ukraine. Practical recommendations arising from the research are presented, including reducing the level of uncertainty for business, revising the tax system, creating incentives for the development of SMBs, and increasing the transparency and stability of the conditions for resource mobilization. Several key principles of the national policy aimed at facilitating conditions for the development of entrepreneurship and anti-corruption are also suggested.